Optimism and Psychological Well-Being from A Positive Psychology Perspective: A Narrative Review - Anlı, Gazanfer; Solak, Mehmet Yavuz Furkan (My University, 2025)
Optimism refers to a positive opinion that good things would happen in the future and that negative situations are temporary or controllable. This concept, which has an important place in positive psychology, is closely related to the concept of psychological well-being, which also has a large influence in this field. Psychological well-being is the ability to reach the best possible level for various aspects in one's world, to strive for it, and to function in different aspects of life. Optimism has functional outcomes in terms of life satisfaction, happiness, positive-negative emotion, social well-being, stress, anxiety, depression, overstimulation, quality of life, and many other related variables. While studies on optimism and psychological well-being occupy an important place in literature, a very few studies exist in Türkiye. The aim of the current study is to compile studies that examine the relationships between these two concepts and present them to the experts in the field. Thus, it is expected that this research will increase the knowledge in the relevant literature and be a resource for researchers in positive psychology and other fields. The studies are discussed in the conclusion section and suggestions for future studies are provided.
Keywords: Resilience; Psychological Well-Being; Optimism; Review; Positive Psychology